Analisis tingkat kepuasan orang tua terhadap pelayanan di TPA Dharma Yoga Santi Yogyakarta - Muthmainah; Nur Cholimah; Eka Sapti Cahya Ningrum; Prayitno, Prayitno (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
The aim of this research is to determine the level of parental satisfaction with services at the Dharma Yoga Santi Yogyakarta Daycare. This research is descriptive quantitative research using a questionnaire as a research instrument. The research respondents were 25 parents. The data was then analyzed quantitatively. The research results showed that: 1) 75% of parents expressed satisfaction and 18.8% stated they were very satisfied with the development achieved by their children, 2) 68.8% of parents stated they were satisfied, and 18.8% stated they were very satisfied with the implementation of the curriculum in the learning process, 3) 62.5% of parents said they were satisfied and 25% said they were very satisfied with the assessment of children's development, 4) 56.3% said they were satisfied and 31.3% said they were very satisfied with the ability of educators to guide children, 5) 56.3% said they were satisfied and 25% said they were very satisfied with communication carried out by educators, 6) 43.8% said they were satisfied and 43.8% said they were very satisfied with the ability of educators to act and behave towards children, 7) 43.8% said they were satisfied and 25% said they were very satisfied with the availability of school infrastructure, 8) 68.8% said they were satisfied, and 25% said they were quite satisfied with the availability of facilities that support children's play activities, and 9) 68.8% said they were satisfied and 25% said they were quite satisfied with the management of daycare facilities and infrastructure. Satisfaction with infrastructure and its management can be further improved to support the stimulation of children's growth and development and increase parents' trust in the institution.